Iowa RBA, August 31- September 4, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Five emails of Iowa RBA updates for August 31 to September 4, 1999. Highlights of the updates include sightings of a Mississippi Kite, Red-necked Phalarope and a Black-throated Blue Warbler. Epson - sheet feed/flatbed